TEKNIK COGNITIVE RESTRUCTURING UNTUK MENINGKATKAN PENERIMAAN DIRI PEREMPUAN MARRIED BY ACCIDENT - Aulina, A; Sa'adah, Nurus (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
Teenage girls who become pregnant out of wedlock face greater pressure than teenage boys who have premarital sex. The psychological impact of this pressure is more significant so its is important to develop sel-acceptance to help them adapt to new situations. The emergence of the term married by accident due to marriage resulting from an unplanned pregnancy, indicates the existence of this phenomenon in society. This research uses a literature riview method with a focus on teh application of conitive restructururing techniques to increase self acceptance in married by accident women. Data was collected through books and online sources such as google scholer, then analyzed descriptively.